Concordance assay between sonographic and histologic findings in breast lesions under Core Needle Biopsy - Farhad yousefi; Donya Farrokh; Seyed Ali Alamdaran; Bita Abbasi; Maryam Salehi; Majid Shams (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Regarding to high prevalence of breast cancer, it is important to find strategies for early, rapid, convenient and accessible diagnosis. After screening and detecting a lesion in the breast, the type of lesion and the degree of malignancy should be determined.This study was performed with aim to evaluate the concordance between sonographic and histologic findings in breast lesions under core needle biopsy. Methods: This cross-sectional prospective study was performed on 149 patients referred to Omid Hospital, Mashhad University of Medical Sciences who underwent core needle biopsy from breast lesions during 2015 to 2018. Patients who had BI-RADS 3, 4, and 5 and according to the surgeon's recommendation required biopsy of the lesion underwent ultrasonically guided biopsy. Also, the lesions which had a malignant sonographic view, but were placed in the benign lesions group after core needle biopsy and histologic examination, were evaluated with excision. Data were analyzed using SPSS software (version 22) and descriptive statistics (frequency distribution table and frequency percentage). Results: The histological findings of BI-RADS 3 lesions were completely benign (11 cases). The frequency of malignancy in lesions with BI-RADS 4 was 31% (39 cases). All cases with BI-RADS 5 were malignant according to histological finding. 8 (44%) of 18 cases with BI-RADS 4b lesions that were benign according to needle biopsy findings were malignant in excisional biopsy findings. Conclusion: In cases that breast lesions are BI-RADS 4b in sonography and the results of core needle biopsy showed benign lesions, additional histological diagnostic evaluation is recommended to rule out malignancy. More studies with higher sample sizes are recommended to confirm the results of this study.